2018
DOI: 10.1111/phn.12529
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ dependence in activities of daily living: Implications for oral health

Abstract: Functional dependence in activities of daily living has implications for the oral health status of older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
(15 reference statements)
1
23
1
Order By: Relevance
“…Our findings did not show significant associations between any ADL and having a dentist, though ADLs have been associated with reduced dental utilization in a Japanese sample and poorer oral healthcare outcomes elsewhere . However, we observed an association with two IADLs, that is, needing help with doing light housework (housekeeping) and needing help with transportation, which might reflect respondents’ lack of social support and the absence of easy access to public transportation, respectively.…”
Section: Discussioncontrasting
confidence: 81%
“…Our findings did not show significant associations between any ADL and having a dentist, though ADLs have been associated with reduced dental utilization in a Japanese sample and poorer oral healthcare outcomes elsewhere . However, we observed an association with two IADLs, that is, needing help with doing light housework (housekeeping) and needing help with transportation, which might reflect respondents’ lack of social support and the absence of easy access to public transportation, respectively.…”
Section: Discussioncontrasting
confidence: 81%
“…Studies of older people have reported associations between oral function and physical or psychological factors, such as nutritional status, physical function, mental function, cognitive function and living function . In contrast, social and environmental factors, such as the association between the number and frequency of social participation and the number of remaining teeth, FGO and oral health awareness, maximal tongue pressure and leisure activities and networks with neighbors, have also been reported, but few reports have focused on oral function and FGO.…”
Section: Discussionmentioning
confidence: 99%
“…This can be because of functional dependency in activities of daily living (ADL) including eating or drinking, brushing teeth, and going to the toilet have implications to oral health. [18] However, it was interesting finding that those who were dependent on care givers to brush their teeth were more likely satisfied with their oral health. This could be either oral health care provided by the staff in the care home were sufficient or the residents have low perceived dental needs due to lack of oral health awareness as they were dependent to the carers for their ADL.…”
Section: Discussionmentioning
confidence: 99%